Flight of Mammals: From Terrestrial Limbs to Wings - Panyutina, Aleksandra A. (Springer eBooks, 2015)
The evolutionary acquisition of flapping flight in mammals remains one of the unresolved questions of biology. Currently, no consensus as to the morphofunctional steps through which mammals passed to gain the ability to fly by flapping wings has been reached.   Flight of Mammals: From Terrestrial Limbs to Wings is the result of several years of research aimed to fill this gap in the literature. Its conclusions are based on original data obtained by dissections of musculoskeletal system of a number of species and on a biomechanical analysis of these data. In addition to a thorough discussion of anatomy and the means through which mammals acquired flapping flight, more than two-hundred detailed line drawings and images provide a picture of the mechanisms of flight in bats and colugos unavailable in any other source.   The book is of interest to a wide range of biologists, not only to those who study bats. The methods and approaches used by the authors can be also applied to other groups of mammals in order to create morphofunctional scenarios of their evolution.   Authors Aleksandra A. Panyutina, Leonid P. Korzun, and Alexander N. Kuznetsov are all followers of the scientific school of functional morphology developed at Department of Vertebrate Zoology, Faculty of Biology, Lomonosov Moscow State University, Moscow, Russia.